he Hybrid Character – Between the Representations of the Middle Ages and Today’s Art - Cezarina Florina Caloian (Anastasis: Research in Medieval Culture and Art, 2020)
This paper is a study of the fantastic character throughout the history of human civilization. This type of character has evolved from the hybrid creatures playing a divine role in the art of Assyro-Babylonian civilizations and of Ancient Egypt, to the monstrous characters of the Middle Ages which served as substitutes for sin and the force of evil, visible in the entrelacs of illuminated manuscripts or the gargoyles guarding the walls of Gothic cathedrals, to the characters of non-human origin in children’s book illustrations, and up to the characters found in fantasy films or today’s hybrids, who are in a perfect relationship with technological and cultural evolution. The paper discusses some original visions and working methods, from the slightly humorous portraits signed by Arcimboldo, the hybridization of animal kingdoms, in a much more tragic register, in the works of Hieronymus Bosch or the fantastic character used as a weapon of political and moral satire in the works of Goya and Grandville, to the unexpected, occult and mysterious visions of Ernst Fuchs’ creations or the imaginary universe populated by hybrid beings, of ‘extra-terrestrial origin, found in the works of HR Giger.